SISTEM PAKAR DIAGNOSA PENYAKIT GINJAL BERBASIS WEB MENGGUNAKAN METODE CERTAINTY FACTOR - Kikye Martiwi Sukiakhy; Sri Azizah Nazhifah; Junidar Junidar (Universitas Nusa Cendana, 2023)
There are still limited health facilities in Indonesia, especially those dealing with kidney disease and the lack of knowledge and information in the community regarding the early symptoms of kidney disease, causing the death rate caused by this disease to continue to increase every year. An expert system that can diagnose kidney disease is urgently needed to provide a solution to this problem with the hope that people can easily obtain information regarding the symptoms of kidney disease they are experiencing, and that people can make a diagnosis independently. A method called the certainty factor (CF) is used in the expert system in this study. Diagnosis of kidney disease based on various symptoms experienced by the user is the output generated by this expert system. Based on the symptoms entered by the user, the system will then look for the highest CF value and then the results will be displayed to the user. The displayed results include 17 symptoms, disease name, diagnosis results and solutions. The functional tests carried out went as expected for the three access rights, namely admin, expert and user can access all functions and no errors were found in the system, using both the Windows 8 and Windows 10 operating systems for admin, expert and user access.